2015
DOI: 10.1093/fampra/cmv048
|View full text |Cite
|
Sign up to set email alerts
|

Symptom perceptions and help-seeking behaviour prior to lung and colorectal cancer diagnoses: a qualitative study

Abstract: Background.Lung and colorectal cancer are common and have high UK mortality rates. Early diagnosis is important in reducing cancer mortality, but the literature on lung and colorectal cancers suggests many people wait for a considerable time before presenting symptoms.Objective.To gain in-depth understanding of patients’ interpretations of symptoms of lung and colorectal cancer prior to diagnosis, and to explore processes leading to help-seeking.Methods.Semi-structured interviews were conducted with patients d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 17 publications
3
49
0
Order By: Relevance
“…22 Importantly, this study highlights how certain factors can act as either barriers or facilitators to diagnosis in different contexts. A similar observation was reported by McLachlan and colleagues 23 in their study of help-seeking behaviour prior to lung and colorectal cancer diagnosis. They observed how health professionals may act as both a barrier and a facilitator to diagnosis.…”
Section: Comparison With Existing Literaturesupporting
confidence: 86%
See 1 more Smart Citation
“…22 Importantly, this study highlights how certain factors can act as either barriers or facilitators to diagnosis in different contexts. A similar observation was reported by McLachlan and colleagues 23 in their study of help-seeking behaviour prior to lung and colorectal cancer diagnosis. They observed how health professionals may act as both a barrier and a facilitator to diagnosis.…”
Section: Comparison With Existing Literaturesupporting
confidence: 86%
“…To assist with this, physicians need to explore patients' understanding of their symptoms. This finding is echoed by McLachlan and colleagues, 23 who found that prompting patients for further information within a consultation may give important details about the context of their symptoms, later aiding physician decision making. The authors further suggest that a more inclusive approach should be taken by physicians to encompass vague symptoms (for example, not just those presented in media campaigns, such as coughs and rectal bleeding) when considering the investigation of patients for potential malignancy.…”
Section: Implications For Research and Practicementioning
confidence: 93%
“…Although they tend to result in increased knowledge levels, the symptom appraisal/help‐seeking interval often remains the same (Tustin, ). People with relevant symptoms who are aware of the campaigns sometimes describe not perceiving the information as relevant to themselves (Caswell et al ., ; McLachlan et al ., ). Furthermore, due to the campaigns’ strong focus on the cough symptom, people often remain unaware of other warning signs such as backache, weight loss, or fatigue (Birt et al ., ; Caswell et al ., ; McLachlan et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Research has indicated that patients in the United Kingdom experience symptoms for several months before presenting to health services (Corner, Hopkinson, Fitzsimmons, Barclay, & Muers, ; Corner, Hopkinson, & Roffe, ; Tod, Craven, & Allmark, ). Reasons for delayed presentation include lack of awareness of symptoms, attribution of symptoms to minor health conditions (e.g., a common cold, a smoker's cough) or ageing, and sometimes fear of finding a serious cause and fatalistic beliefs about lung cancer (Brindle, Pope, Corner, Leydon, & Banerjee, ; Corner et al ., , ; Lyratzopoulos, Liu, Abel, Wardle, & Keating, ; McCutchan, Wood, Edwards, Richards, & Brain, ; McLachlan et al ., ; Shim, Brindle, Simon, & George, ; Smith, Pope, & Botha, ; Tod & Joanne, ; Walton et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests lack of knowledge about lung cancer symptoms is one of the biggest barriers to help-seeking [7,9-14]. Furthermore, symptoms are often masked by preexisting comorbidities that have similar symptoms, making it difficult for the patient to distinguish between existing and new symptoms [12,15].…”
Section: Introductionmentioning
confidence: 99%